A unique opportunity for food systems transformation in Rwanda - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Rwanda has made remarkable progress in the past two decades, highlighted by rapid economic growth and sharp reductions in poverty. During this period, the country emerged as a leader among sub-Saharan African countries in promoting innovation, gender equality, and an enabling business environment. The government remains strongly committed to ambitious development goals, efficiency and transparency in implementation, strong collaboration with the private sector, and diplomacy through regional and global partnerships.